Risk assessment of heavy metals bioaccumulation: fished shrimps from the Persian Gulf. (2nd October 2017) - Shahsavani, Abbas; Fakhri, Yadolah; Ferrante, Margherita; Keramati, Hassan; Zandsalimi, Yahya; Bay, Abotaleb; Hosseini Pouya, Seyedeh Rokhsane; Moradi, Bigard; Bahmani, Zohreh; Mousavi Khaneghah, Amin
Abstract: Although, several benefits can be offered by the consumption of marine products, the heavy metals bioaccumulation inside of their body can put the health of consumers at a high level of risk. In this context, however, the Persian Gulf contentedly is polluted by waste water, solid waste and petroleum activities residues, due to an increasing trend in consumption of fished aquatic organisms such as fish and shrimp, the safety of marine products is a source of concern. The current review was established in order tracing the metals concentrations in the muscle of fished shrimps from the Persian Gulf as well as conducting the health risk assessment. The reviewed literature was based on the internal and external databases. According to the results of 23 studies, the maximum and minimum heavy metals concentrations were determined as Zn (8.56 ± 34.68 μg/g) and Hg (0.08 ± 0.04 μg/g), respectively. Moreover, the heavy metal levels in the 32.5% of studies were higher than premiered limit by the WHO/FDA guidelines. Based on the calculated median for heavy metals concentrations, Total target hazard quotient (TTHQ) for the adults and children were reported as 0.466 and 0.311, respectively. The order of the concentration of the heavy metals can be demonstrated as following: Co > As > Cd > Pb > Cu > Zn > Mn > Ni > Hg > Cr. Considering the results of risk assessment, no potential human health risk for the consumer's shrimps of the Persian Gulf was observed. Research highlights Maximum and minimum of heavy metals concentrations in the shrimps were determined as Zn and Hg, respectively, in the Bushehr, Khuzestan, Bandar Abbas, Qeshm Island, Kuwait and Qatar. Total target hazard quotient for the adults and children were less than 1 value. Overall, potential health risk of heavy metals does not threaten consumer's heath.